Quantitative Analysis of Catch-up Saccades Executed during Two-dimensional Smooth Pursuit - Laurutis, V.; Daunys, G.; Zemblys, R. (Elektronika ir Elektrotechnika, 2010)
The purpose of this research was to investigate quantitatively the catch-up saccades occurring during smooth pursuit. In our experiment, to evoke catch-up saccades we used two-dimensional non-predictable time-continuous target trajectories submitted with 3 peak velocities: 12.5, 25 and 50deg/s. From the experimental results we computed the relationships of the parameters of catch-up saccades: the amplitude, the peak velocity, the time interval between two-saccades in the bunch of them with the parameters such as the position error, the retinal slip and the transient and integral target velocities. On the basis of the analysis of these relationships, we proposed the model how catch-up saccades are programmed and how the slow (smooth pursuit) and the rapid (saccadic) eye movements interact. Ill. 6, bibl. 5 (in English; summaries in English, Russian and Lithuanian).